Time and Speed of Vascular Pedicle Dissection in Deep Inferior Epigastric Artery Perforator Flap Elevation - Yim, Ji Hong; Lee, Yeon Hoon; Kim, Young Chul; Kim, Eun Key; Lee, Taik Jong; Yun, Jiyoung; Eom, Jin Sup (Journal of Reconstructive Microsurgery, 2017)
Background Breast reconstruction using deep inferior epigastric artery perforator (DIEP) free flap is widely used because of the advantages of minimizing donor-site morbidity, but it requires technical competency in vascular dissection. This study evaluated the influence of patient factors and vascular status on the time and speed of dissection of the vascular pedicle.Methods DIEP free flap procedures were performed in 49 patients assigned to immediate or delayed reconstruction groups. Factors that significantly influenced the time required and the speed of dissection were evaluated. Results The average total dissection time was 55.9 minutes (34.5 minutes for the intramuscular dissection and 21.4 minutes for the submuscular dissection). The dissection speed for the total vascular pedicle was 2.65 cm/10 minutes (1.71 cm/10 minutes for the intramuscular dissection and 4.30 cm/10 minutes for the submuscular dissection). The presence of a Pfannenstiel scar, length of the vascular pedicle in the intramuscular area, and the number of microclips used significantly correlated with the total dissection time. Conclusion The length of the intramuscular pedicle, number of microclips used, and presence of a Pfannenstiel scar significantly correlated with the total dissection time of the vascular pedicle. An assessment prior to the surgery can reduce the time of operation and make it easier to elevate the flap.
Keywords: autologous breast reconstruction; deep inferior epigastric artery perforator free flap; dissection of vascular pedicle; dissection time and speed